Tax Avoidance: Analisis Earnings Mangement dan Capital Intensity dimoderasi Sales Growth - Ratna Hindria Dyah Pita Sari; Ahmad Rifaldi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2022)
Abstract This research is motivated by a decrease in the realization of taxes received in Indonesia in the 2017-2019 period. The decrease in tax realization is indicated by the existence of tax avoidance actions carried out by companies, especially in manufacturing companies that have been listed on the Indonesia Stock Exchange by adding fixed assets and earnings management, so that it can be formulated that how the influence of earnings management and capital intensity on tax avoidance is moderated by sales growth. This study aims to examine the effect of earnings management and capital intensity on tax avoidance with sales growth as a moderating variable. This study uses a sample, namely manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used in this study, namely the purposive sampling method with the acquisition of a sampling of 123 samples. The data analysis technique used in this study uses multiple regression analysis and moderation regression analysis with results showing that earnings management and capital intensity have a significant effect on tax avoidance. Meanwhile, sales growth cannot moderate earnings management and capital intensity on tax avoidance. Kata Kunci :